A study on chlorophyll, total carotenoid and beta-carotene contents in carrot and the effect of climate on them - Alireza Ebadollahi-Natanzi; Gholamreza Arab-Rahmatipour (Institue of Medicinal Plants, ACECR, 2020)
Background: Carotenoids are pigments with important physiological effects in the human body that are involved in strengthening the immune system and reducing the risk of many diseases, including cancer. Objective: With regard to the importance of these substances and the high content of them in carrots (Daucus carota L.), and in order to identify the most suitable geographical area for obtaining the products with the highest levels of these compounds, the present study was carried out. Methods: Samples were collected and investigated from six major carrot cultivation regions, located in Khuzestan and Isfahan provinces. The effects of climate changes on the amount of these substances were also studied. The extracts were prepared from the samples and the experiments were performed by spectrophotometric method at 663, 645, 480 and 436 nm wavelength, repectively. Results: The highest mean of total chlorophyll content in leaves (1.42 mg/g) and total carotenoids (54.62 μg/g) and beta-carotene (24.97 μg/g) in plant roots were related to Andimeshk in Khuzestan province, and the lowest amounts of them was related to Dastgerd in Isfahan province with average of 0.61 mg/g, 18.72 μg/g and 1.98 μg/g, respectively. Conclusion: The results of this study showed that in Khuzestan province, parameters such as temperature (23.5-25 °C), relative humidity (49.5-58 percent) and rainfall (260-570 mm/year) had better conditions for carrot metabolic activity and consequently having caused a significant increase in carotenoids and beta carotene in this plant product.